Admission Blood Pressure Severity as a Predictor of Stroke Subtype and Early Neurological Deterioration: A Retrospective Cohort Study - Ikhsan, Maulana; Asmaul Husna, Cut (Fakultas Kedokteran Universitas Malikussaleh, 2025)
This study investigated the significance of admission systolic blood pressure (SBP) severity as a predictor of stroke subtype and early neurological worsening in a group of 220 acute stroke patients. We conducted a retrospective analysis, classifying entry systolic blood pressure in accordance with American Heart Association standards and assessing outcomes related to stroke subtype (hemorrhagic versus ischemic) and early neurological deterioration (END), the latter extracted from clinical notes. Upon controlling for age, sex, diabetes, and cholesterol, we observed that admission systolic blood pressure was markedly elevated in individuals with hemorrhagic stroke. Every 10 mmHg elevation in systolic blood pressure (SBP) augmented the adjusted odds of hemorrhagic stroke by 42%, whereas patients experiencing a hypertensive crisis (SBP ≥180 mmHg) exhibited a five-fold increased likelihood of hemorrhagic stroke relative to normotensive individuals. A hypertensive crisis was independently linked to an almost three-fold elevation in the likelihood of early neurological impairment. The correlation was most pronounced in individuals below 50 years of age. We determine that the severity of entry systolic blood pressure is a significant, independent predictive marker for hemorrhagic stroke subtype and early clinical deterioration, highlighting its essential function in acute stroke evaluation and treatment.